Transfer Factor of Radionuclides from Soil to Leafy Vegetables in Iraq Using Gamma Ray Spectroscopy - Jameel, Athraa Naji (Iraqi Journal of Science, 2023)
The activity concentration of natural radioactivity levels, of artificial cesium and transfer factor from soil to plants in agricultural areas at Al- Yusiefya region were determined by using NaI (Tl) detector spectrometer. Ten species of leafy plants have been selected: Spinach, Parsley, Watercress, Lettuce, Rashad, Radish, Green onion, Turnip green, Green beet and Mint. The mean activity concentrations of 238U, 232Th, 40K and 137Cs in leafy vegetable samples were  12.4±3.8, 14.8±4.7, 283±93 and 1.06±0.99  Bg/kg, and in soil samples were 15.9±4.3, 16.1±5.2, 298.5±3.9, and 1.11±0.37 Bq/kg. The radiation hazard indices were evaluated (radium equivalent, external hazard index, annual effective dose, absorbed dose rate) were within the permissible values except for excess lifetime cancer risk. The mean transfer factor values of 226 Ra, 232Th, 40K, and 137Cs were 0.89±0.2, 0.9±0.2 , 1.02±0.3, and 0.77±0.25. The leafy vegetable are safe for consumption and the studied area does not pose a considerable radiological threat .